Penyuluhan Peraturan Daerah Kalimantan Timur No 7 Tahun 2019 Tentang Adaptasi dan Mitigasi Perubahan Iklim - Arief Muliawan; Ahmad Yani (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2021)
East Kalimantan Province is very vulnerable to climate change, so it needs policies and strategies in managing climate change impacts through adaptation and mitigation actions. So it is necessary to stipulate local regulations on climate change adaptation and mitigation. Management of climate change in East Kalimantan is one of the local government's efforts in providing guarantees to the community to get a quality living environment. The purpose of this community service activity is to provide understanding to residents regarding East Kalimantan Regional Regulation No. 7 of 2019 concerning climate change adaptation and mitigation. The method of implementing this community service activity is in the form of counseling and discussion of East Kalimantan Regional Regulation No. 7 of 2019 concerning climate change adaptation and mitigation. Based on the results of community service activities related to the extension of East Kalimantan Regional Regulation No. 7 of 2019 regarding climate change adaptation and mitigation, it was concluded that many people still do not know about the regional regulation. Efforts to mitigate and adapt to climate change are not only the responsibility of the Government, but also the responsibility of the DPR. The DPR's climate change mitigation and adaptation efforts can be carried out through the implementation of its three functions, namely the budget function, the supervisory function, and the legislative function. Every stakeholder, including the community, must mitigate and adapt to climate change, because adaptation and mitigation is the key to addressing climate change, which is the key to reducing greenhouse gas emissions and increasing carbon stocks to reduce the impact of climate change. The active role of the regional government in formulating policies related to climate change is a must, the policy is expected to be a direction for stakeholders in East Kalimantan.